Method for applying starch to a paper or paperboard web
The use of a water-based suspension with uncooked starch and parent-type polymers for foam coating addresses uneven distribution and inefficiencies in starch application, improving adhesive strength and reducing environmental impact in paper production.
Patent Information
- Application Number
- JP2021567938
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-14
- Filing Date
- 2020-05-13
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2040-05-13
AI Technical Summary
Conventional methods for applying starch in paper production face issues such as uneven distribution, high liquid usage, energy inefficiency, and environmental contamination due to uncooked starch particles, particularly in multilayer sheet paper production, where uncooked starch is used at the wet end.
A method involving a water-based suspension containing uncooked starch particles and a parent-type polymer is used to create a foam coating, which is then applied to the paper web using non-impact coating techniques, allowing for higher solid content and improved adhesive strength between layers.
This method reduces drying costs, minimizes environmental impact, and enhances inter-layer strength in multilayer sheet paper by providing a uniform and efficient application of uncooked starch particles, avoiding the drawbacks of conventional liquid coating methods.
Smart Images

Figure 0007624407000001 
Figure 0007624407000002 
Figure 0007624407000003
Abstract
Description
[Technical field]
[0001] This invention relates to the manufacture of paper or paperboard, and in particular to the application of starch to a paper or paperboard web. [Background technology]
[0002] Starch is an important non-fibrous material used in the papermaking process. Starch is utilized during the industrial papermaking process at several steps by several different methods to achieve the desired results. For example, starch can be added to the pulp before sheet formation, it can be sprayed between the layers of multi-layered paperboard, and it can be applied onto the surface of the paper for surface sizing. Sources of starch include plants such as corn, wheat, barley, potato, and tapioca, whose tubers, seeds, etc. are the source of starch.
[0003] For use as an interply adhesive in the manufacture of multi-ply paperboard, such as cup stock, starch is used at the wet-end in the form of starch granules, i.e., in the form of uncooked starch. Starch can be added at the wet-end or at the latest stage on the surface before assembling the multiple plies. The use of uncooked starch at the wet-end between the plies of multi-ply paperboard has been found to be effective in increasing the bond strength of the plies. However, uncooked starch in the form of starch granules is only applied on the wet paper or paperboard web before the drying section where the starch is then cooked. The interply starch application is generally done by spray or curtain coating of the solution. Both spray and curtain methods depend on the rheological properties, solids content, and liquid formulation. Spray application is usually done using low viscosity liquids, resulting in low solids content. In addition, spray application generates a lot of dust, thus causing contaminants and deposits, which lead to microbial growth in the paperboard environment. Dosing a dilute solution onto a paper or paperboard web is not cost effective and can lead to uneven distribution and unnecessary wetting.
[0004] Starch is also used in sizing paper and paperboard. Many paper processes utilize a surface treatment known as sizing. Typically, this is accomplished by applying a thin layer of starch after the paper has been dried in a section of the paper machine known as the size press. The majority of the total starch is applied by the size press on the surface of the paper. The surface sizing treatment fills voids in the paper sheet and improves surface strength as well as surface integrity and printability. Dry-end sizing of paper or paperboard utilizes the application of cooked starch. Starch is often added in cooked form on top of the dried paper.
[0005] To alleviate the problems caused by the large amounts of liquid media used in conventional surface treatments, foam coating has been proposed. In foam coating, a foam is used as a carrier phase for the applied chemicals or drugs. The foam is mechanically broken after application to the surface of the paper or paperboard. EP2744728B1 for example discloses a process for applying a barrier coating on paperboard, the coating mixture being preferably applied by foam coating. This barrier can be combined with another barrier structure based on a biobarrier, such as a starch or polysaccharide-based barrier. However, the teaching of the document does not give any suggestion of applying starch via a foam coating method. WO2016 / 207783A1 discloses a method for producing a film of nanofibrillated polysaccharides by using a foam formation containing an amphiphilic polymer. However, this teaching refers to the wet-end process of producing a paper web and does not relate to the foam coating method or the application of starch particles. WO2018 / 011667A1 discloses a process for making a foam and using the foam in a foam coating process for making paper or board products. The coating uses an antimicrobial starch. However, the teachings of the document do not mention uncooked starch particles. Summary of the Invention [Problem to be solved by the invention]
[0006] Thus, there continues to be a need for methods that are suitable for wet-on-wet application, i.e., application to a wet web, while allowing for higher solids to be applied. [Means for solving the problem]
[0007] This object is met with the method and paper or paperboard product according to the present invention. The dependent claims relate to preferred embodiments. They can be freely combined, unless the context clearly indicates otherwise.
[0008] The present invention provides the following: 1. A method for applying starch to a paper or paperboard web comprising the steps of: - providing an aqueous suspension comprising starch particles and at least 1% by weight, based on the dry solids content of the aqueous suspension, of an amphiphilic polymer; - forming a foam of said aqueous suspension; and - applying said foam to a web of paper or paperboard. The method includes: DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The aqueous suspension for foam formation comprises particles of starch and an amphiphilic polymer. Surprisingly, it has been found that it is possible to use foam coating techniques to apply starch particles, i.e. particles of uncooked or partially uncooked starch, to a web of paper or paperboard when the foam composition further comprises an amphiphilic polymer. Without being bound to a particular theory, it is assumed that the amphiphilic polymer offers the possibility of using foam coating of starch particles at high solids. Foams made from suspensions of particulate uncooked starch using an amphiphilic polymer unexpectedly gave much higher solids of starch compared to the use of surfactants such as sodium dodecyl sulfate (SDS) that are typically used as foaming additives. This is particularly unexpected considering that suspensions of uncooked particulate starch were used to generate the foam. Furthermore, the use of amphiphilic polymers allows the generation of foams that are free or essentially free of surfactants, in particular oil-based surfactants such as SDS.
[0010] A further important advantage of this method is that a foam coating of starch with a high solid content can be applied between the layers of the multi-layer paperboard, thereby providing improved adhesion and increased interlayer strength of the paperboard. This is particularly advantageous compared to liquid coating of low solid content solutions, which require the application of large amounts of liquid to the web, which further requires subsequent drying and the respective energy consumption. Further cost savings are possible due to reduced drying costs, for example due to improved drainage. This method allows the administration of starch particles between the layers of the multi-layer paperboard, or as a surface treatment on a wet paper / paperboard web. The method of applying starch particles to a paper or paperboard web using a foam coating technique achieves several advantages. This method can be used for wet-on-wet administration. This method allows the application of higher solids, which also results in lower drying costs. This method avoids contamination and build-up problems in the paperboard environment. And this method allows the production of multi-layer paperboard that provides improved interlayer strength.
[0011] As used herein, "paper" and "paperboard" refer to a paper-based substrate of an amalgamation of fibers that may include at least partially vegetable, wood, and / or synthetic fibers. The paper or paperboard web preferably comprises cellulose fibers. The web preferably comprises cellulose fibers from hardwoods (broadleaf) and / or softwoods (coniferous). The paper or paperboard web may have a basis weight in the range of, for example, 15 to 150 gsm, or 20 to 150 gsm. The basis weight of the final paper or paperboard may range from 30 to 800 gsm.
[0012] The term starch as used herein refers to starch derived from plant materials that are commonly used in the paper industry and may be rice, barley, wheat, potato, corn, or tapioca starch. The term starch granule refers to starch that has not been cooked to completely dissolve, i.e., in the form of a soluble polymer, but in its native, pre-gelatinized, or partially gelatinized granular form. Such "uncooked" or partially uncooked starches include particulate starch materials that can be identified, for example, under a microscope. The term uncooked starch means that the starch has not been cooked, such that a major portion of the starch particles can be seen under an optical microscope. Even native and uncooked forms of starch tend to swell, especially when stored at higher pH or elevated temperatures. That is, uncooked starch may also swell to some extent. Thus, the term starch granule as used herein also includes gelatinized or swollen starch. All forms of swollen and native particles can be identified under an optical microscope. The particle size of starch can be measured, for example, using laser light scattering or low-angle laser light scattering. One example is the Mastersizer 2000 particle size analyzer (Malvern, UK), which measures the percentage of total starch volume in a specific diameter size interval. Other methods for measuring average particle size are, for example, optical image analysis. The use of starch in the methods discussed herein is carried out on such starch particulate material.
[0013] The term "amphiphilic polymer" refers to so-called surface-active polymers, which have both hydrophilic and hydrophobic (or lipophilic) groups. The amphiphilic or surface-active polymers may be so-called hydrophobic surface-active polymers. According to one embodiment, the amphiphilic polymer has a molecular weight (Mw) of more than 20000 g / mol, preferably more than 40000 g / mol or more than 50000 g / mol. This contributes to increasing the solids content of the foam formed. The amphiphilic polymer may also have a cloud point in the range of 40-80°C, which further improves the stability of the foam formed. According to one embodiment, the amphiphilic polymer is selected from the group of ethyl hydroxyethyl cellulose (EHEC), hydrophobically modified (HM) ethyl hydroxyethyl cellulose (HM-EHEC), hydroxyethyl cellulose (HEC), hydrophobically modified hydroxyethyl cellulose (HM-HEC), hydroxypropylated cellulose (HPC), hydrophobically modified carboxymethyl cellulose (HM-CMC), hydrophobically modified starch (HM-starch), hydroxypropylated starch, or combinations or mixtures thereof. The amphiphilic polymer may also be selected from the group of octenyl succinic anhydride (OSA) starch, dodecyl succinic anhydride (DDSA) starch, carboxymethyl cellulose (CMC) with hydrophobic properties, or combinations or mixtures thereof. These amphiphilic polymers have been shown to be particularly advantageous and are furthermore biodegradable. According to further embodiments, the amphiphilic polymer may be selected from the group of hydrophobically modified polyvinyl alcohols (PVOH), such as ethylene modified PVOH or PVOH modified with silanol, cationic or carboxyl functional groups. According to further embodiments, the amphiphilic polymer may be a polyvinyl alcohol containing 2% or more acetate groups, or containing 10% or more acetate groups, preferably containing 15% or more acetate groups. The amphiphilic polymer may also be a charged amphiphilic polymer. The charge may promote retention. The amphiphilic polymer may also be a mixture of these different amphiphilic polymers.The term "amphiphilic polymer" further refers to polymers that tend to self-associate, such as synthetic block copolymers and proteins. Amphiphilic polymers can also be polyelectrolytes that have been physically grafted, for example, by sorption or precipitation or crosslinking or ion exchange, for example with metal salts or oppositely charged polymers.
[0014] In some embodiments, the aqueous suspension comprises the amphiphilic polymer in an amount ranging from 0.5% to 30% by weight, preferably from 1% to 10% by weight, based on the dry solids content of the suspension. The aqueous suspension may comprise the amphiphilic polymer in an amount ranging from 1% to 5% by weight, based on the dry solids content of the suspension. These amounts of amphiphilic polymer, such as ethyl hydroxyethyl cellulose, have been shown to provide advantageous high solids content of the suspension foam.
[0015] Sodium dodecyl sulfate (SDS) is usually used as a foaming aid. Advantageously, the use of an aqueous suspension allows foams to be created in the absence of surfactants such as SDS, making it possible to avoid or greatly reduce the use of SDS. In particular, the high solids content of the suspension foam was achieved without adding SDS to the suspension. The aqueous suspension is preferably free or substantially free of oil-based surfactants such as SDS, sodium dodecylbenzenesulfonate (SDBS), meaning that the amount of these oil-based surfactants is less than 1% by weight based on the dry solids content of the suspension. Advantageously, this allows for improved adhesion between layers, since oil-based surfactants can cause weak bond layers and thus inhibit adhesion. It has been shown that foams can be formed at higher solids content when the composition includes a surface-active polymer but is substantially free of oil-based surfactants. Without being bound to a particular theory, it is believed that surfactant-free suspensions allow for higher interlayer strength.
[0016] The amphiphilic polymers can be used in combination with other agents useful for creating and / or stabilizing foams. The aqueous suspension may include a co-additive, for example an additive selected from gelled and / or dissolved starch, nanocellulose, fillers, and nanopigments. As used herein, "fillers" refers to inorganic particulate materials used in papermaking, as typically referred to in the papermaking industry. The term nanopigments refers to nanoscale powders, thus having at least one dimension with an average particle size in the range of 1-100 nm. The pigments may be selected from clays and / or talcs. The aqueous suspension may include an amount of co-additive in the range of 0.01% to 70% by weight, or in the range of 0.01% to 50% by weight, or in the range of 0.01% to 30% by weight, or in the range of 0.01% to 10% by weight, based on the dry solids content of the suspension.
[0017] The aqueous suspension may comprise nanocellulose, i.e. nanofibrillated or microfibrillated cellulose. In a preferred embodiment, the aqueous suspension comprises microfibrillated cellulose (MFC). Microfibrillated cellulose (MFC) is also known as nanocellulose. The term usually refers to material obtained from wood cellulose fibres, both from hardwood (broadleaf) or softwood (coniferous) fibres. It can also be obtained from microbial sources, agricultural fibres such as wheat straw pulp, bamboo, or other non-wood fibre sources. In microfibrillated cellulose, the individual microfibrils are partially or completely separated from each other. The fibrils of microfibrillated cellulose are usually very thin, for example around 20 nm, and their length is often between 100 nm and 10 μm. The microfibrils can also be longer, for example between 10 and 200 μm, but lengths as long as 2000 μm can also be found due to a wide length distribution. The definition of MFC also includes fibers that are fibrillated and have microfibrils on the surface, as well as microfibrils that are separated and present in the aqueous phase of the slurry. Furthermore, cellulose whiskers may also be included in the definition of MFC. The fibrils may also be polymer-coated fibrils, i.e. chemically or physically modified fibrils. Advantageously, microfibrillated cellulose (MFC) is useful for stabilizing foams and / or for avoiding the penetration of the applied starch suspension into the paper or paperboard web. The microfibrillated cellulose (MFC) may be applied in an amount ranging from 0.01% to 70% by weight, or from 0.01% to 50% by weight, or from 0.01% to 30% by weight, or from 0.01% to 10% by weight, based on the dry solids content of the suspension. The aqueous suspension may contain further functional chemicals such as colorants, pigments, crosslinkers, humectants, etc.
[0018] Unless otherwise stated, the percentages given are weight percent (wt%) and are calculated based on either 100% dry weight or 100% total weight of each object, such as a suspension. The total amount of each component does not exceed 100% by weight. It is further understood that the remainder of an aqueous suspension is water, bringing the total weight of the aqueous suspension to 100% by weight.
[0019] The aqueous suspension comprises starch in the form of starch particles. The suspension may comprise starch granules. In some embodiments, the aqueous suspension comprises starch particles in an amount ranging from 30% to 99% by weight, or from 50% to 99% by weight, preferably from 70% to 99% by weight, or from 90% to 99% by weight, based on the dry solids content of the suspension. The aqueous suspension before foaming comprises a large amount of starch particles. In some embodiments, the suspension comprises amphiphilic polymer in an amount ranging from 1% to 10% by weight, and starch particles in an amount ranging from 30% to 99% by weight, or from 50% to 99% by weight, or from 70% to 99% by weight, or from 90% to 99% by weight, based on the dry solids content of the suspension.
[0020] Native starch particles may be further granulated to achieve a particular particle size prior to use, but the starch remains in its granular form. In some embodiments, the starch particles have a median particle size in the range of 0.5 μm to 200 μm. Surprisingly, it has been found that such large particles can be used in foam applications. The median particle size may be at least 1 μm or at least 2 μm. Preferably, the median particle size is in the range of 1 μm to 200 μm, more preferably in the range of 2 μm to 200 μm. Starch particles can be processed into smaller particle size starches, for example by classification or mechanical or chemical modification. The average particle size of starch varies depending on the source, but can usually be in the range of 10 μm to 30 μm. As used herein, the term "median particle size" (D 50) refers to the particle size above which 50 percent (by volume) of the starch particles are greater and 50 percent below which particle size. Particle sizes referred to herein refer to particle sizes measured using a Mastersizer 2000 particle size analyzer (Malvern, UK) in dilute aqueous suspension at pH 5-9, electrolyte concentrations of 0.001-0.01 M NaCl, and temperatures of 20-25°C.
[0021] The starch may be natural or modified. In one preferred embodiment, the starch is a natural starch. The starch particles may also be nanostarch, such as nanostarch available from Ecosynthetix. The term nanostarch refers to starch granules with particle sizes in the nanometer range. Mixtures of starch and natural starch nanoparticles may also be used. Advantageously, the starch particles may vary widely in particle size and / or have a wide particle size distribution (particle size distribution).
[0022] The aqueous suspension containing starch particles and amphiphilic polymer is in the following method steps used to create a foam. The term foam refers to a two-phase system of gas bubbles separated by liquid lamellae. The creation of the foam can be achieved by any conventional means, such as by stirring as a mechanical operation or by adding foam-forming chemicals as a chemical operation. The foam can be obtained by stirring the aqueous suspension in the presence of air, for example with a stream of air or with the aid of an agitator. The foam can be created using high pressure air. A conventional foam generator can be used to generate the foam.
[0023] It has been shown that the method allows for the achievement of surprisingly high solids content of stable foams containing starch granules. In some embodiments, the solids content of the aqueous suspension foam is 5% or more, preferably 10% or more, more preferably 15% or more, based on 100% total weight of the suspension foam. The solids content of the aqueous suspension foam can be in the range of 5% to 50% by weight, 5% to 40% by weight, or 5% to 20% by weight, based on 100% total weight of the suspension foam. The solids content of a given foam is related to the solids content of the starch. The solids content can be measured using methods known in the art, such as drying and weighing, such as using an IR dryer.
[0024] In some embodiments, the density of the foam in the aqueous suspension is 10 g / 100 ml or more, preferably greater than 14 g / 100 ml.
[0025] In the next method step, the foam is used to coat the paper or paperboard web. The advantage of using the foam is that the foam-coated particles have an improved tendency to remain on the surface of the web. This can result in less penetration of the starch particles into the web. The created foam prevents the coated starch from penetrating into the structure of the paper or paperboard during production, giving the foam, and more specifically the air bubbles in the foam, an advantage that is particularly valuable for surface-sized starches.
[0026] The foam can be applied using coating techniques commonly used in papermaking processes such as cast coating or blade coating. However, it is preferred to apply the foam to the substrate by using a non-impact coating technique. The term "non-impact" coating refers to coating procedures that avoid contact between the mechanical elements of the applicator head and the paper or minimize the contact pressure during application. This provides considerable advantages in terms of runnability, such as avoidance of possible web breaks, surface quality, and defects such as streaks. The term "non-impact" coating is not intended to exclude subsequent gentle leveling by rods, blades, or air jets. In some embodiments, the foam is applied to the paper or paperboard web by a non-impact coating technique selected from spray coating, curtain coating, or foam coating. Curtain coating and spray coating offer advantages over conventional blade or roll coating by eliminating streaks and reducing the risk of web breaks. The preferred application method is spray coating. This application method efficiently avoids the destruction of the previously formed layer or web. Most preferred is foam coating. The foam application method allows for the use of high dry content. Foam coating offers the advantage of applying a thin coating onto the surface of the web, e.g., at a coating weight of less than 2 gsm. Foam coating may be applied to the paper or paperboard web using a foam coating applicator or coater.
[0027] The method allows for the administration of starch particles between the layers of a multi-layer paperboard or as a surface treatment on a wet paper / paperboard web. The application of starch particles according to the method can be carried out at the wet end and / or the dry end of the paper or paperboard manufacturing process. The method is useful for providing a surface sizing to a paperboard web with starch particles. Thus, the method may participate in an improvement of the process of surface sizing paper and paperboard. The method is further particularly useful for administering starch between the layers in the manufacture of multi-layer paperboard. Thus, the method may further participate in an improvement of the process of manufacturing multi-layer paperboard.
[0028] In some embodiments, the foam is applied to a paper or paperboard web having a solids content of less than 50% by weight, preferably less than 70% by weight, based on 100% by weight of the total weight of the paper or paperboard web.
[0029] The method can be used to apply surface sizing to a paperboard web with starch particles. In some embodiments, the method is a method of surface sizing a paper or paperboard web. In a surface sizing application, the foam can be applied to a wet web, such as having a solids content of less than 50% by weight, preferably less than 85% or 90% by weight, prior to the drying section.
[0030] In a preferred embodiment, the method is a method for dosing starch between layers in the manufacture of multi-layer paperboard. In these embodiments, starch particles are applied to a wet web before it is attached to another web. The method of the present invention allows for improved interlayer strength. In addition to improving the interlayer adhesion, board conversion is also improved due to better coverage and more uniform spreading of the starch granules. Another possibility that opens up when dosing starch between layers with the present invention is that in the manufacture of paperboard, starch can be applied to the web not only when the web is running horizontally, but also when the web is running vertically. This is often more practically done during the manufacturing process.
[0031] The coating weight applied is 0.1 g / m 2 More than ~30g / m 2 The following range, preferably 0.5 g / m 2 More than ~20g / m 2 The range is preferably 1 g / m 2 More than ~10g / m 2 The weight or basis weight of the coating can be in grams per square meter, gsm or g / m 2 The weight is expressed as
[0032] As used herein, gsm and g / m 2 can be used interchangeably. The method of the invention advantageously allows the application of thin layers, while still achieving good coverage. The respective applications can be carried out with foam coating equipment, curtain coating equipment or spray coating equipment.
[0033] The invention further relates to a paper or paperboard product obtained by the method of the invention. The paper or paperboard product comprises at least one starch layer applied via foam coating of a foam obtained from an aqueous suspension comprising starch particles and at least 1% by weight of an amphiphilic polymer based on the dry solids content of the aqueous suspension. The paper or paperboard product may comprise at least one starch layer applied on at least one surface and at least one layer.
[0034] In some embodiments, the paper or paperboard product has a viscosity of 0.1 g / m 2 More than ~30g / m 2 The following range, preferably 0.5 g / m 2 More than ~20g / m 2 Less than 1 g / m, more preferably 2 More than ~10g / m 2 It comprises at least one starch layer having a coating weight in the following ranges: The coating weights given refer to dry weight.
[0035] The starch is applied to the paper or paperboard web in the form of particles. After the starch is applied during a subsequent manufacturing process, the paper or paperboard web may be heated and the starch cooked and gelatinized on the paper or paperboard web. Thus, the manufactured paper or paperboard product comprises at least one starch layer, where the starch may be uncooked starch and / or cooked or gelatinized starch. The manufactured paper or paperboard product preferably comprises a layer of cooked or gelatinized starch.
[0036] The starch layer can be applied as a sizing layer or as an interlayer. In some embodiments, the paperboard product is a multi-layer paperboard. The paper or paperboard product can include at least one layer, preferably several layers, such as a top layer and a back layer, and at least one middle layer. The paper or paperboard product can include several middle starch layers, such as two or three middle starch layers. Multi-layer paperboard can advantageously provide improved adhesion of multiple layers.
[0037] In a further embodiment, the paperboard product is a surface-sized paper or paperboard. The paper or paperboard product may include at least one surface-sized layer. The sized layer applied by the present method via foam coating using starch particles and amphiphilic polymers can advantageously provide a very uniform starch sized layer with minimal roughness.
[0038] The paperboard product may be a multi-layered paperboard, including at least two plies, a top ply and a back ply, and preferably at least one middle ply or several middle plies. The paperboard product may have a basis weight ranging from 30 to 800 gsm. The paper or paperboard produced may be any type of paper or paperboard, such as liquid packaging board, folding box board, stiff bleached board, stiff unbleached board or container board. One possible product is corrugated paper, where the web is either a liner or a corrugated paperboard, and the aqueous suspension comprising the starch particles and the amphiphilic polymer is an adhesive that is applied to attach the corrugated paperboard to the liner. EXAMPLES
[0039] Further features of the present invention will become apparent from the following examples.
[0040] Materials and methods The materials used to generate the aqueous coating suspension were uncooked starch granules (barley, Altia Plc, Finland), hydrophobically modified hydroxyethylcellulose (EHEC, Bermocoll EHM200, AkzoNobel Chemicals AG, Sweden), and sodium dodecyl sulfate (SDS, Merck KGaA, Germany). The particle size distribution (by volume) of the uncooked starch granules used is shown in Table 1. The particle sizes were measured at pH approx. 7 and temperature 23°C using a Mastersizer 2000 particle size analyzer (Malvern, UK).
[0041] [Table 1]
[0042] Cupforma classic 210 gsm was used as the substrate. The starch was mixed as received without further processing in cold water. The foam was produced using A Rollmix BGR13 (Rollmac, Italy). The coating of the substrate was done using a bench coater (rod).
[0043] Prior to foam production, the pH and viscosity of the aqueous suspensions were measured. The viscosity of the foams was measured with a Brookfield Digital Viscometer (Model DVII+, Brookfield Engineering Laboratories, Inc.) using spindle #6 at speeds of 10 rpm and 50 rpm at the temperatures shown in the table below. Spindle #1 and 50 rpm were used to measure the viscosity of the aqueous suspensions, except for sample 6, which used 10 rpm. The solids content was measured with an IR dryer. The sample volume was approximately 1 g. The density of the foams was measured by dividing the measured weight of the foam by the measured volume.
[0044] Reference Examples 1 and 2 Reference Examples 1 and 2 were carried out to evaluate the foaming ability of aqueous suspensions without the addition of foam-generating agents in laboratory tests. The ingredients and properties of the suspensions of Reference Examples 1 and 2 are summarized in Table 2.
[0045] [Table 2]
[0046] The suspensions of Reference Examples 1 and 2 did not foam, confirming that no foaming is observed without the additive.
[0047] Examples 3 to 6 A series of tests were carried out to evaluate the foaming ability of suspensions containing uncooked starch particles and amphiphilic polymers according to the invention. Experiments were carried out using EHEC as the foaming agent. The ingredients and properties of the aqueous suspensions of Examples 3-6 are summarized in Table 3.
[0048] [Table 3]
[0049] In addition to pH and viscosity, the solids content of the foams was measured for Examples 5 and 6. These examples provided aqueous starch solutions with 12% and 18% solids by weight, respectively. The solids content was measured with an IR dryer. The sample amount was about 1 g. As can be seen in Table 2, the starch content in the foams of Examples 5 and 6 was very high. The EHEC-based foams were stable and did not completely break down during the coating operation. Furthermore, the breakage of the EHEC foams during coating was more inhibited.
[0050] This demonstrates that not only is it possible to use foam coatings using uncooked starch, but that the production of surfactant-free foams can be achieved with much higher starch contents than expected, a significant improvement over the prior art which uses SDS as a surfactant.
[0051] Reference examples 11~14 A series of tests were also carried out to evaluate the foaming behavior of aqueous starch solutions using SDS as the foaming agent. The ingredients and properties of the aqueous suspensions of Reference Examples 11 to 14 are summarized in Table 4.
[0052] [Table 4]
[0053] The foam of Reference Example 11 using 1 wt% SDS broke almost immediately. However, the foam of Reference Example 12 using 5 wt% SDS was very stable and did not break when coated with a rod. However, increasing the solids content in the liquid suspension to 12 wt% and 18 wt% did not result in a higher foam solids content when using SDS foam, as seen in Reference Example Samples 13 and 14, where the foam solids content remained low. Also, water separated immediately. This indicates that SDS as a foaming agent only leads to poor foam production and the starch content in the foam is lower.
[0054] Reference examples 15~18 A further series of tests was carried out to evaluate the foaming behavior of aqueous starch solutions without foaming agent. The ingredients and properties of the aqueous suspensions of Examples 15 to 18 are summarized in Table 5.
[0055] [Table 5]
[0056] These references demonstrate that viscosity increases as solids content increases. Various aspects or embodiments that can be included in the present invention are summarized as follows. [1]. 1. A method for applying starch to a paper or paperboard web comprising the steps of: - providing an aqueous suspension comprising starch particles and at least 1% by weight, based on the dry solids content of the aqueous suspension, of an amphiphilic polymer; - creating a foam of said aqueous suspension; and - applying said foam to a web of paper or paperboard. The method includes: [2]. 2. The paperboard of claim 1, wherein the amphiphilic polymer is selected from the group of ethyl hydroxyethyl cellulose, hydrophobically modified ethyl hydroxyethyl cellulose, hydroxyethyl cellulose, hydrophobically modified hydroxyethyl cellulose, hydroxypropylated cellulose, hydrophobically modified carboxymethyl cellulose, hydrophobically modified starch, hydroxypropylated starch, or combinations or mixtures thereof. [3]. The method according to item 1 or 2, wherein the aqueous suspension contains the amphiphilic polymer in an amount ranging from 1% by weight to 10% by weight based on the dry solid content of the suspension. [4]. 4. The method according to any one of items 1 to 3, wherein the aqueous suspension comprises starch particles in an amount ranging from 30% to 99% by weight, or from 50% to 99% by weight, preferably from 70% to 99% by weight, or from 90% to 99% by weight, based on the dry solids content of the suspension. [5]. 5. The method according to any one of items 1 to 4, wherein the starch particles have a median particle size in the range of 0.5 μm or more and 200 μm or less, preferably in the range of 1 μm or more and 200 μm or less, and more preferably in the range of 2 μm or more and 200 μm or less. [6]. 6. The method according to any one of items 1 to 5, wherein the aqueous suspension contains microfibrillated cellulose. [7]. The method according to any one of items 1 to 6, wherein the solid content of the foam of the aqueous suspension is 5 wt % or more, preferably 10 wt % or more, and more preferably 15 wt % or more, based on 100 wt % which is the total weight of the foam of the aqueous suspension. [8]. 8. The method according to any one of the above items 1 to 7, wherein the foam is applied to the paper or paperboard web by a non-impact coating technique selected from spray coating, curtain coating, or foam coating. [9]. 9. The method according to any one of the above items 1 to 8, wherein the foam is applied to a paper or paperboard web having a solids content of less than 50% by weight, preferably less than 70% by weight, based on 100% by weight, the total weight of the paper or paperboard web.
[10] . The method according to any one of the above items 1 to 9, wherein the method is a method for surface sizing a paper or paperboard web.
[11] . The method according to any one of the above items 1 to 9, wherein the method is a method for administering starch between layers in the manufacture of multi-layer paperboard.
[12] . A paper or paperboard product obtained by the method according to any one of items 1 to 11 above.
[13] . The paper or paperboard product has a viscosity of 0.1 g / m 2 More than ~30g / m 2 The following range, preferably 0.5 g / m 2 More than ~20g / m 2 The range is preferably 1 g / m 2 More than ~10g / m 2 13. The paper or paperboard product according to item 12 above, comprising at least one starch layer having a coating weight in the following range:
[14] . 14. The paper or paperboard product according to claim 12 or 13, wherein the paperboard product is a multi-layer paperboard.
[15] . 15. The paper or paperboard product of any one of the above items 12 to 14, wherein the paperboard product is a surface sized paper or paperboard.
Claims
1. 1. A method for applying starch to a web of paper or paperboard, excluding starch having hydrophobic groups, comprising the steps of: - providing an aqueous suspension comprising starch particles in an amount ranging from ≧30% to ≦99% by weight based on the dry solids content of the aqueous suspension, and at least 1% by weight of an amphiphilic polymer based on the dry solids content of the aqueous suspension; - creating a foam of said aqueous suspension; and - applying said foam to a web of paper or paperboard Including, the amphiphilic polymer is selected from the group of ethyl hydroxyethyl cellulose, hydrophobically modified ethyl hydroxyethyl cellulose, hydroxyethyl cellulose, hydrophobically modified hydroxyethyl cellulose, hydroxypropylated cellulose, hydrophobically modified carboxymethyl cellulose, hydrophobically modified starch, hydroxypropylated starch, or combinations or mixtures thereof; The solid content of the foam of the aqueous suspension is 10% by weight or more based on 100% by weight, which is the total weight of the foam of the aqueous suspension; The method wherein the foam is applied to a paper or paperboard web having a solids content of less than 50% by weight, based on 100% by weight of the total weight of the paper or paperboard web.
2. The method of claim 1, wherein the aqueous suspension comprises the amphiphilic polymer in an amount ranging from ≧1% to ≦10% by weight based on the dry solids content of the suspension.
3. 3. The method of claim 1 or claim 2, wherein the aqueous suspension comprises starch particles in an amount ranging from ≧50% to ≦99% by weight based on the dry solids content of the suspension.
4. The method according to any one of claims 1 to 3, wherein the starch particles have a median particle size in the range of 0.5 µm or more and 200 µm or less.
5. The method according to any one of claims 1 to 4, wherein the aqueous suspension comprises microfibrillated cellulose.
6. The method according to any one of claims 1 to 5, wherein the solids content of the foam of the aqueous suspension is 15% by weight or more, based on 100% by weight of the total weight of the foam of the aqueous suspension.
7. The method of any one of claims 1 to 6, wherein the foam is applied to the paper or paperboard web by a non-impact coating technique selected from spray coating, curtain coating, or foam coating.
8. The method according to any one of claims 1 to 7, wherein the method is a method for surface sizing a web of paper or paperboard.
9. The method according to any one of claims 1 to 7, wherein the method is a method for dosing starch between plies in the manufacture of multi-ply paperboard.
10. A paper or paperboard product obtained by the method according to any one of claims 1 to 9.
11. The paper or paperboard product has a viscosity of 0.1 g / m 2 More than 30g / m 2 11. The paper or paperboard product of claim 10 comprising at least one starch layer having a coating weight in the following range:
12. 12. The paper or paperboard product of claim 10 or 11, wherein the paperboard product is a multi-ply paperboard.
13. The paper or paperboard product of any one of claims 10 to 12, wherein the paperboard product is a surface sized paper or paperboard.
Citation Information
Patent Citations
Production method of liner for corrugated card board
JP2009228173A
Method for producing core base paper for corrugated board
JP2009293138A
Method for producing a film or film product containing an amphiphilic polymer
JP2018520273A
Manufacturing method for a film or product comprising an amphiphilic polymer
US20180355557A1
Polysaccharide Adhesive
US20190010302A1